Effect of seed moisture content and storage temperature on seed longevity of hemp (Cannabis sativa) - PARIHAR, S S; DADLANI, M; LAL, S K; TONAPI, V A; NAUTIYAL, P C; BASU, SUDIPTA (The Indian Journal of Agricultural Sciences, 2014)
Hemp (Cannabis sativa L.) is one of the earliest domesticated plants grown for its protein and oil rich seed, fiber and psychoactive substances and it is one of the earliest known medicinal plants in human history. Studies were conducted on seed germinability (germination test) and viability (topographical tetrazoliun chloride test) in three seed lots to determine the seed quality. Studies conducted on effect of five seed moisture contents (5, 7, 8, 10 and 12 % on fresh weight basis), three storage temperature (ambient, 15°C and -20°C) and eight storage periods (0, 3, 6, 9, 12, 18, 24 and 36 months) on seed longevity revealed that the critical moisture content (moisture content required in seeds for retaining initial germination after storage of seeds up to 36 months) of seeds for ambient storage condition of Delhi was 5 %, which increased to 7 % in 15°C and 12 % at -20°C storage temperature. The seeds are desiccation as well as chilling tolerant, therefore, exhibit orthodox storage behavior and are ideal for ex-situ conservation of seeds in seed/gene banks.